Supporting accessible technology-enhanced training: The eaccess2learn framework - Sampson, Demetrios; Zervas, P. (2011)
During the last years, the design and development of technology-enhanced training systems for disabled groups of learners has attracted the attention of the technology-enhanced learning community. However, although a number of such systems have been designed to meet accessibility needs and preferences for those groups, most of them anticipate special-purpose e-training material and keep their e-training activities local to the particular system in use. As a result, neither reuse of existing digital training resources (widely available nowadays in web-based repositories) nor sharing of best technology-facilitated training practices among the communities of educational practitioners and training organizations is supported by these systems. Within this context, in this paper, we present the eAccess2Learn Framework which aims at providing tools and services that facilitate the design and development of accessible e-training resources and courses that bare the potential to be interexchanged between different e-training platforms and programs, thus making them potentially exploitable and reusable between different disabled user groups. © 2008 IEEE.